Deliberative Planning Analysis: Study on Policy-Making Inhibiting Factors in Musrenbangdes - Rahmat Rafinzar; Zailani Surya Marpaung; Khairunnas Khairunnas; Rizky Ghoffar Ismail (Universitas Teuku Umar, 2023)
The success of the Musrenbangdes policy implementation will always be determined by various factors. Inhibiting factors are often the cause of the ineffective implementation of a policy. This research was conducted to look at the inhibiting factors in making Musrenbangdes policy which is seen in the scope of deliberative planning. This study uses a descriptive research method with a qualitative approach. The data analysis techniques used by the researchers are interactive models from Miles and Huberman. Research conducted in Pulau Rimau District, Banyuasin Regency, South Sumatra found that there were inhibiting factors in the implementation of Musrenbangdes that led to the decision-making process in deliberative planning. Some of these factors are the involvement of community interest groups that have not been fully involved or are still in the form of representatives. Determination of participant representatives in Musrenbangdes has not been seen based on age group which causes inclusiveness of public involvement to be not created. In addition, public involvement has not been seen based on socio-economic backgrounds such as education, employment, and the strategic location of activity locations. This has an impact on the deliberative planning process that has not been able to run effectively and inclusively. The involvement of interest groups, age groups, social and economic backgrounds of the community is important to consider in determining Musrenbangdes participants to create a deliberative planning process that accommodates all stakeholders.